Training and testing the elite athlete - Bangsbo, J.; Mohr, M.; Poulsen, A.; Perez-Gomez, J.; Krustrup, P. (Journal of Exercise Science & Fitness, 2006)
The performance of a top-class athlete can be improved by appropriate training. The fitness training should be closely related to the activities of the athlete during competition. Furthermore, the capacity of the athlete should be known. For that purpose, Yo-Yo tests can be used since they have been shown to be sensitive and to give valid measures of performance in many sports. The fitness training can be divided into aerobic, anaerobic and specific muscle training. Each type of training has a number of subcategories, which allows for a precise execution of the training when the aim of the training is known. A critical factor when training elite athletes is when to do what, i.e. to plan the training. An example of the preparation of the Danish National soccer team for the European Championship 2004 is given in the text with examples of physiological measurements and testing, which also takes individuals` needs into account.